Ocean politics in Southeast Asia - Polomka, Peter (Institute of Southeast Asian Studies, 1978)
The seas of the world are increasingly exciting and taxing mankind's imagination in terms of their potential beniefits and wealth, as well as inherent dangers of mismanagement and regional and international maritime conflict. The waters of Southeast Asia are no so than most other comparable areas.